Use of TOF-SIMS in Vascular Biology - Mas, Sebastian; Pérez, Raúl; Egido, Jesús (My University, 2013)
Secondary ion mass spectrometry is a technique used for surface analysis. The recent introduction of metal cluster ionization sources opened the possibility to probe biological tissues, due to its reduced in-source fragmentation. Despite its limitations in mass range of the molecules analyzed, a combination of minimal sample processing, sensibility, and unsurpassed lateral resolution makes TOF-SIMS a good tool for molec ular imaging in pathology. Key words Atherosclerosis , Imaging , Lipidomics , Metabolomics , SIMS-TOF